Properties and environmental impact of recycling cigarette butts (CBs) in fired clay brick - Sarani, Noor Amira (2014)
Brick is one of the man-made building materials that have been used since the early human civilization. Due to the attractive appearance, strength and durability, it often used for construction, civil engineering works and landscape design. This study is focused on the effects of incorporating cigarette butts (CBs) into fired clay brick. The investigation includes characterization, optimum percentage of CBs incorporated, physical and mechanical properties, leachability and indoor air quality. Therefore, clay soil samples obtained from Hoe Guan Brick Sdn Bhd were used as control in this research while 2.5% and 5.0% by weight of CBs were incorporated into the clay bricks for subsequent experiments. Different heating rates were used during the firing processes which are 1 C/min respectively. All samples were fired at 1050 o o C/min, 3 o C/min and 5 C. The results suggested that the heating rates of 1 o o C/min with 2.5% CBs are adequate to achieve optimum properties. The results also indicated that the maximum compressive strength of fired clay brick was obtained with 2.5% CBs of fired clay brick at 1 C/min heating rate compared to others. The density becomes lightweight by 16% to 21% compared to conventional bricks as the percentage of CBs increased. The thermal conductivity of the bricks also improved from 24.6% to 46.1% with the increasing of CBs. In addition, leachability results indicated that the leaching of heavy metals were below the United States Environmental Protection Agency (USEPA) and Environmental Protection Agency Victoria (EPAV) regulations. Finally, laboratory testing for Indoor Air Quality (IAQ) revealed that CB Brick complied with the Industry Code of Practice on Indoor Air Quality (ICOP-IAQ).